A review of R-DHAP administration in the outpatient setting and a case of the alternative regimen R-DHAX given outpatient for refractory diffuse large B-cell lymphoma. (December 2019) - Hill, Hailey; Arnall, Justin; Janes, Amanda; Hatley, Crystal; Swift, Kristen; Hargett, Christy; Howell, Theresa; Griffin, Sarah; Larck, Christopher; Park, Stephen
Introduction: Several regimens for treating hematologic malignancies are given inpatient due to multiple factors. Many clinicians are evaluating methods to deliver traditionally inpatient regimens in the outpatient setting to increase patient satisfaction, improve access to therapy, and reduce costs. A regimen traditionally administered inpatient, dexamethasone, cytarabine, and cisplatin (DHAP) is a common and effective salvage regimen for relapsed/refractory non-Hodgkin's lymphoma. DHAX, which substitutes oxaliplatin for cisplatin, has been identified as a reasonable alternative to DHAP and offers the potential for tolerable administration in the outpatient setting as well. Case description: A 74-year-old patient with double hit relapsed/refractory diffuse large B cell lymphoma was given rituximab, dexamethasone, high-dose cytarabine, and oxaliplatin (R-DHAX) in our outpatient clinic; however, this regimen is traditionally administered in the inpatient setting. Our main obstacle being cytarabine doses traditionally given 12 h apart. The outpatient regimen given to our patient was rituximab and oxaliplatin on day 1, cytarabine dose one late afternoon on day 2, cytarabine dose two early morning on day 3, and dexamethasone on days 1–4. Doses of oxaliplatin and cytarabine were reduced due to thrombocytopenia experienced with Cycle 1. He did not experience any increased toxicities or complications associated with the regimen moving forward. Discussion: This illustrates a unique administration of R-DHAX in an infusion center that operates during typical outpatient clinic hours. Both DHAP and DHAX, with or without rituximab, administered in the outpatient setting may be options to consider in relapsed/refractory non-Hodgkin's lymphoma.